Quality Assurance in Breast Health Care and Requirement for Accreditation in Specialized Units - GÜLLÜOĞLU, MAHMUT BAHADIR (My University, 2014)
Breast health is a subject of increasing importance. The statistical increase in the frequency of breast cancer and the consequent increase in death rate increase the importance of quality of services to be provided for breast health. For these reasons, the minimum standards and optimum quality metrics of breast care provided to the community are determined. The quality parameters for breast care service include the results, the structure and the operation of services. Within this group, the results of breast health services are determined according to clinical results, patient satisfaction and financial condition. The structure of quality services should include interdisciplinary meetings, written standards for specific procedures and the existence of standardized reporting systems. Establishing breast centers that adopt integrated multidisciplinary working principles and their cost-effective maintenance are important in terms of operation of breast health services. The importance of using a "reviewing/auditing" procedure that checks if all of these functions existing in the health system are carried out at the desired level and an "accreditation" system indicating that the working breast units/centers provide minimum quality adequacy in all aspects, is undeniable. Currently, the accreditation system for breast centers is being used in the European Union and the United States for the last 5-10 years. This system is thought to provide standardization in breast care services, and is accepted as one of the important factors that resulted in reduction in mortality associated with breast cancer.
Keywords: accreditation; breast center; Breast health; quality assurance